2016
DOI: 10.1590/s0100-204x2016000900066
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbiological properties and available nitrogen for corn in monoculture and intercropped with forage

Abstract: -The objective of this work was to evaluate the effects of corn (Zea mays) in monoculture and intercropped with forage on soil microbiological properties and nitrogen availability under no-tillage in the Cerrado (Brazilian savanna). The experiment was carried out from the 2007/2008 to the 2010/2011 crop season, in a Latossolo Vermelho-Amarelo distrófico (Typic Haplustox). A randomized complete block design with three replicates was used, with the following treatments: corn in monoculture; corn intercropped wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
1
6
0
2
Order By: Relevance
“…Nos sistemas agrícolas, essa entrada/saída de carbono é muito influenciada pelo preparo do solo, espécies utilizadas, rotações de culturas, adubação e, principalmente, pelo manejo dos resíduos das culturas (COSER et al, 2016;CAMPOS et al, 2011).…”
Section: Introductionunclassified
“…Nos sistemas agrícolas, essa entrada/saída de carbono é muito influenciada pelo preparo do solo, espécies utilizadas, rotações de culturas, adubação e, principalmente, pelo manejo dos resíduos das culturas (COSER et al, 2016;CAMPOS et al, 2011).…”
Section: Introductionunclassified
“…GAÚCHA,v.25,n.3, MOS em sistema de semeadura direta e afirmam que sistemas mais conservacionistas tendem a incrementar a matéria orgânica do solo na superfície ao longo do tempo. As diferenças observadas nos teores de matéria orgânica do solo nos primeiros anos de condução do experimento se devem à entrada e saída de carbono no sistema de cultivo, o que é influenciada pelo preparo do solo, espécies utilizadas e rotação de culturas (COSER et al, 2016;CAMPOS et al, 2011). Houve uma diminuição da densidade do solo para todos os tratamentos (Figura 4), esse resultado é explicado pela mudança no uso do solo, passando de cultivo de pastagem para cultivo agrícola.…”
Section: Resultsunclassified
“…Plant quality composition, litter deposition and root realeased exsudates are possible parameters that affect microbial biomass dynamics [17,40]. Coser et al [11] found an Brazilian Archives of Biology and Technology. Vol.62: e19170737, 2019 www.scielo.br/babt average MBC content (192.0 mg kg -1 ) for all management systems in the same site during 2010/2011 season evaluation, with significative differences in P. maximum and maize-P. maximum intercropping (248.0 mg kg -1 and 210.0 mg kg -1 .…”
Section: Chemical and Microbiological Soil Attributesmentioning
confidence: 99%
“…For Cerrado biome (Brazilian savanna), however, which accounts for 45% of maize production1 and 26% of pasture lands in Brazil [9], the consortium of maize with forage species has been of growing interest, mainly to anticipate the establishment of pastures and increase the soil cover in no-tillage management in areas destined to crop-livestock systems [10]. Intercropped maize with Panicum maximum increased soil microbial biomass nitrogen and microbial nitrogen quotient compared to maize in monoculture, resulting in higher nitrogen availability [11]. Indeed, a significant portion of the positive aspects provided by the intercropping seems to be directly related to the increased population of beneficial microorganisms.…”
Section: Introductionmentioning
confidence: 99%